The Effect of Cardinal Traits on Compulsive Buying on Zara Product Purchases in Jakarta-Bandung - Shyfa Diana Yulianti Situmorang; Hariyadi Triwahyu Putra (Journal of Social Research, 2024)
This study aims to examine the effect of cardinal traits on compulsive buying mediated by hedonistic shopping. The research objects set in this study are women and men aged 18-60 years who have bought and used Zara brand clothing products in Jakarta and Bandung. The research methodology used was quantitative methodology, by making Likert scale questionnaires, in the number of research respondents as many as 125 people. This research phase is a classical assumption test, multiple regression, hypothesis test, and sobel test using an online calculator from Preacher with the help of statistical program of social science (SPSS) version 26. The results showed hedonistic shopping that successfully mediated two cardinal traits variables, including extraversion, and openness to compulsive buying, it is hoped that this study will gain knowledge about strategies that must be done to regulate and assess compulsive buying